Nursing care in the relationship knowledge/power and sexuality with school youth via web radio - Leidy Dayane Paiva de Abreu; Glícia Mesquita Martiniano Mendonça; Aretha Feitosa de Araújo; Raimundo Augusto Martins Torres; Maria Rocineide Ferreira da Silva; Ana Virgínea de Melo Fialho (Universidade Federal de Santa Maria, 2019)
Objective: To describe the experience of postgraduate nursing students about sexuality and the knowledge-power relationship with school pupils via Web Radio. Method: the experience emerged in "Micropolitics" subject, held at the first semester of 2016, in articulation with Foucault's Knowledge/Power theoretical and philosophical framework and the topic sexuality. Results: in the experience it is seen that the school and the health department are configured as spaces of resistance. There is no teacher/nurse/youth speech about sexuality. It was concluded that the Web Radio health care device is an interdiscursive network, involving singularities, providing care practices to young people. Final considerations: Nursing, in this school setting, expands its autonomy of care with the youth in the construction of interdiscursive knowledge.